ATOMS: ALMA Three-millimeter Observations of Massive Star-forming regions – XI. From inflow to infall in hub-filament systems. Issue 4 (25th June 2022) - Zhou, Jian-Wen; Liu, Tie; Evans, Neal J; Garay, Guido; Goldsmith, Paul F; Gómez, Gilberto C; Vázquez-Semadeni, Enrique; Liu, Hong-Li; Stutz, Amelia M; Wang, Ke; Juvela, Mika; He, Jinhua; et al.
ABSTRACT: We investigate the presence of hub-filament systems in a large sample of 146 active proto-clusters, using H 13 CO + J = 1-0 molecular line data obtained from the ATOMS survey. We find that filaments are ubiquitous in proto-clusters, and hub-filament systems are very common from dense core scales (∼0.1 pc) to clump/cloud scales (∼1–10 pc). The proportion of proto-clusters containing hub-filament systems decreases with increasing dust temperature ( T d ) and luminosity-to-mass ratios ( L / M ) of clumps, indicating that stellar feedback from H ii regions gradually destroys the hub-filament systems as proto-clusters evolve. Clear velocity gradients are seen along the longest filaments with a mean velocity gradient of 8.71 km s −1  pc −1 and a median velocity gradient of 5.54 km s −1  pc −1 . We find that velocity gradients are small for filament lengths larger than ∼1 pc, probably hinting at the existence of inertial inflows, although we cannot determine whether the latter are driven by large-scale turbulence or large-scale gravitational contraction. In contrast, velocity gradients below ∼1 pc dramatically increase as filament lengths decrease, indicating that the gravity of the hubs or cores starts to dominate gas infall at small scales. We suggest that self-similar hub-filament systems and filamentary accretion at all scales may play a key role in high-mass star formation.